MISCONCEPTIONS IN SOLVING INDEFINITE INTEGRALS FOR NONELEMENTARY FUNCTIONS USING THE TAYLOR SERIES - Lutfi, Mohammad (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2016)
MISCONCEPTIONS IN SOLVING INDEFINITE INTEGRALS FOR NONELEMENTARY FUNCTIONS USING THE TAYLOR SERIES